Forced nonlinear vibration of shallow shell and application to technical diagnosis - Thach, Le Ngoc; Lien, Tran Van (Vietnam Journal of Mechanics, 2006)
This paper presents direct and inverse problems of forced nonlinear vibration of shallow shell. From that the method of establishment and solution of technical diagnosis for shallow shell under the vibrated load is proposed. The diagnosis criterion is the minimum of the difference between the square of experimental and theoretical data. The diagnosed parameters are the external loads and the reactions arose at the boundaries.